The judicial system of Ethiopia: the case of ațebiya-dańa (local judge), 1940s–1960s - Ayele Tariku Mesheshsa (Cogent Arts & Humanities, 2024)
This research explored the history of Ațebiya-Dańa, village judge in Ethiopia, from 1947 to the 1960s. The research delved into the role of Ațebiya-Dańa in resolving disputes, administering justice, and maintaining social order in Ethiopian communities. The research examined the impact of modernization and political change on the institution of Ațebiya-Dańa during the period. The research employed a multi-method approach that combines historical research, oral history, archival research and group interviews. Historical documents, such as court records, government reports, and scholarly literature, were analysed to provide a historical context for Ațebiya-Dańa. The research provided a comprehensive understanding of the history, role, and impact of Ațebiya-Dańa in Ethiopian society from 1947 to the 1960s. It shed light on the dynamics between traditional justice systems and modern legal institutions, and the challenges and opportunities faced by traditional authorities in the face of modernization and state intervention. The institution, Ațebiya-Dańa had important roles for conflict resolution, social order, and legal pluralism in Ethiopia and other African societies.